The Legal Regime of Joint Ownership in Management as a Tool for Enhancing State Investment Attractiveness - Oleh Prostybozhenko; Mykola Chabanenko; Tetiana Voloshanivska; Nataliia Fedorchenko; Viktor Diektiarov (Nusantara: Journal of Law Studies, 2026)
This study examines the legal regime of joint ownership in management and its impact on a state’s investment attractiveness, focusing on the Ukrainian context. It aims to assess how joint ownership structures affect the efficiency of civil transactions and the reliability of property rights protection, both of which are key determinants of investor confidence. The research applies a doctrinal legal approach, combining the dialectical method to uncover structural contradictions within joint ownership and the formal-legal method to analyze existing legislative norms. Empirical evidence is drawn from aggregated statistical data on property disputes in Ukrainian courts, as well as indicators of investment activity and international investment rankings. The findings show that joint ownership, while economically rational for resource consolidation, generates significant legal and practical inefficiencies. Statistical analysis indicates that disputes related to joint ownership—particularly property division and determination of usage order—consistently constitute one of the largest categories of civil cases, confirming the systemic and recurring nature of the problem. These disputes are not incidental but reflect structural weaknesses in legal regulation, especially the absence of clear, accessible, and efficient procedures for terminating joint ownership. As a result, co-owners frequently face prolonged litigation, increased transaction costs, and legal uncertainty. This condition directly reduces asset liquidity, limits their marketability, and disrupts the smooth functioning of civil turnover. Furthermore, investment data demonstrate a strong correlation between the effectiveness of property rights enforcement and investor sensitivity, where legal uncertainty in ownership regimes negatively influences investment decisions and risk assessments. This study contributes by empirically demonstrating the linkage between deficiencies in joint ownership regulation and reduced investment attractiveness. It highlights the urgency of reforming legal mechanisms governing ownership termination and management to enhance legal certainty, minimize disputes, and strengthen the overall investment climate.